Low-voltage current differencing transconductance amplifier in a novel allpass configuration - Uygur, A.; Kuntman, H. (MELECON 2006 - 2006 IEEE Mediterranean Electrotechnical Conference, 2006)
In this paper, a CMOS realization of the current differencing transconductance amplifier in the low voltage is presented. The proposed circuit can operate in supply rails down to plusmn0.75 V. In the input stage, flipped voltage followers are used to obtain very low input resistances and a few tens of ohms of input resistances are achieved. Then, the proposed circuit is employed in a novel allpass configuration. To verify the correctness of the realization, SPICE simulation results are also supplied